Prevalence and risk factors of thyroid-associated ophthalmopathy among Indians - Mathur, Chetan; Singh, Shailendra; Sharma, Saurabh (International Journal of Advances in Medicine, 2016)
Background: Thyroid-associated ophthalmopathy (TAO) is a part of an autoimmune process that can affect the orbital and periorbital tissue, the thyroid gland, and, rarely, the pretibial skin or digits. The aim of the present study was to determine the prevalence of TAO among Indian patients with thyroid dysfunction and the risk factors associated with TAO. Methods: A cross-sectional study of thyroid eye disease was conducted on patients with thyroid dysfunction visiting the outpatient department of a tertiary care centre. Demographic data, past medical history, family history, and life-style data were collected from all patients. An ophthalmologist interviewed the patients and noted the presence of symptoms and signs relevant to thyroid eye disease. Results: Out of a total of 100 patients, who were eligible for analysis, 80 were diagnosed with mild to moderate TAO and 20 were diagnosed with severe TAO. There were more male patients in patients with a severe course (50%) compared to those with a mild to moderate course (42.5%). More patients with a severe course were smokers compared to those with a mild to moderate course (chi-square test, p=0.021). More patients with a severe course had a higher clinical activity score (p=0.007). Conclusions: We have confirmed that smoking is the strongest risk factor for development of a severe course of TAO in Indian patients. Thus, it is important for patients with Graves’ disease to refrain from smoking.